2008
DOI: 10.1111/j.1471-4159.2008.05736.x
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Differential effects of 24‐hydroxycholesterol and 27‐hydroxycholesterol on tyrosine hydroxylase and α‐synuclein in human neuroblastoma SH‐SY5Y cells

Abstract: Loss of dopaminergic neurons and α-synuclein accumulation are the two major pathological hallmarks of Parkinson’s disease (PD). Currently, the mechanisms governing depletion of dopamine content and α-synuclein accumulation are not well understood. We showed that the oxysterol 27-hydroxycholesterol (27-OHC) reduces the expression of tyrosine hydroxylase (TH), the rate-limiting enzyme in dopamine synthesis, and increases α-synuclein levels in SH-SY5Y cells. However, the cellular mechanisms involved in 27-OHC eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 99 publications
(139 reference statements)
0
59
0
Order By: Relevance
“…Indeed, 7-ketocholesterol and 7b-hydroxycholesterol are found at high levels in atherosclerotic plaques (Garcia-Cruset et al, 1999, in the plasma of patients with cardiovascular diseases (Zieden et al, 1999;Zhou et al, 2000), and in the plasma of subjects tested after a fat-rich meal (Emanuel et al, 1991). In addition to atherosclerosis, it is now suggested that oxysterols could also contribute to the development of other important diseases including neurodegenerative diseases such as Alzheimer's disease (Björkhem, 2006;Cao et al, 2007;Vaya and Schipper, 2007), Parkinson's disease (Bosco et al 2006;Rantham Prabhakara et al, 2008), and multiple sclerosis (Diestel et al, 2003;Leoni et al, 2005), as well as age-related diseases such as age-related macular degeneration (Malvitte et al, 2006) and cataract (Girao et al, 1998) (Table 1). In these diseases, inflammation is a major driving force, and it has been suggested that the oxidation of cholesterol in oxysterols could be a crucial step for the development of cellular stress and tissue damage leading to the initiation and development of these pathologies (Leonarduzzi et al, 2008).…”
Section: Associated Oxysterols Referencesmentioning
confidence: 98%
“…Indeed, 7-ketocholesterol and 7b-hydroxycholesterol are found at high levels in atherosclerotic plaques (Garcia-Cruset et al, 1999, in the plasma of patients with cardiovascular diseases (Zieden et al, 1999;Zhou et al, 2000), and in the plasma of subjects tested after a fat-rich meal (Emanuel et al, 1991). In addition to atherosclerosis, it is now suggested that oxysterols could also contribute to the development of other important diseases including neurodegenerative diseases such as Alzheimer's disease (Björkhem, 2006;Cao et al, 2007;Vaya and Schipper, 2007), Parkinson's disease (Bosco et al 2006;Rantham Prabhakara et al, 2008), and multiple sclerosis (Diestel et al, 2003;Leoni et al, 2005), as well as age-related diseases such as age-related macular degeneration (Malvitte et al, 2006) and cataract (Girao et al, 1998) (Table 1). In these diseases, inflammation is a major driving force, and it has been suggested that the oxidation of cholesterol in oxysterols could be a crucial step for the development of cellular stress and tissue damage leading to the initiation and development of these pathologies (Leonarduzzi et al, 2008).…”
Section: Associated Oxysterols Referencesmentioning
confidence: 98%
“…Oxidized cholesterol derivatives, which are essentially aldehydes, are toxic substances that speed up the aggregation of S ␣ and perpetuate the cycle of degeneration [78] . Moreover, a recent study reported that 27-OH-cholesterol reduces tyrosine hydroxylase and increases ␣ -synuclein expression in neuronal cell cultures [79] . Statins were shown to reduce ␣ -synuclein aggregation in an in vitro model of PD [80] .…”
Section: Normalization Of Cerebral Cholesterol Metabolismmentioning
confidence: 99%
“…More intriguingly, the monomeric form of all three peptides, mHTT, Ab, and a-synuclein, is intrinsically unstructured, whereby the secondary structures are unlikely to spontaneously fold into well-organized globular structures [17]. In the case of both Ab and a-synuclein, the influence of different types of lipids has been shown to accelerate or stabilize the formation of fibrils like betasheets [18][19][20][21][22][23][24][25].…”
mentioning
confidence: 99%